DE INDRE GRÆNSER: Forestillinger om kultur og subkultur i sociale konstruktioner af hiv/aids i Danmark - Jöhncke, Steffen (Tidsskriftet Antropologi, 1996)
Steffen Johncke: The Boundaries Within. Ideas about Culture and Subculture in Social Constructions of HIV/AIDS in Denmark. Based on two studies with practical purposes, this article presents critical analyses of some of the social and political processes involved in the construction of “gay men” and “immigrants” as culturally distinet groups in relation to HIV/AIDS in Denmark. First an evaluation of a campaign that offers information and support to men who have sex with men is presented. The campaign is based with a gay organisation, and it works from the assumption that men who have sex with men belong to a “homosexual subculture”, although they do so in various degrees. This assumption is challenged by the experiences and opinions of members of the target group interviewed in the cause of the evaluation. The subculture imagery, however, coincides with a dominant construction in Danish HIV/AIDS policy: the distinetion between homosexual men and the general (heterosexual) population as separate entities. This distinetion impedes the delivery of relevant information to all men who have sex with men. The second study is concemed with Danish service providers’ view of immigrants living with HIV in Denmark. The service providers’ characterizations of immigrants and accounts of problems of contact are shown to express stereotypical images of “immigrants’ cultural backgrounds”. These images are analysed as the inverted expressions of the social and cultural norms typical of the clinics and offices of the Danish health and social services. In order to improve communication and services, the Danish staff do not need “more knowledge of more cultures”, as they request - rather they need to do critical self-reflection of their relationship with all clients and patients. The article concludes that anthropologists need to be wary of the role played by the concept of “culture” in relation to HIV/AIDS where it has become a political rather than an analytical tool.